Introducing ‘Anthropocene Science’: A new international journal for addressing human impact on the resilience of planet earth - Abhilash, Purushothaman C.; Bastianoni, Simone; Chen, Weiqiang; DeFries, Ruth S.; Fraceto, Leonardo F.; Fuckar, Neven S.; Hashimoto, Shizuka; Hunter, Danny; Keesstra, Saskia; Merah, Othmane; O'Farrell, Patrick J.; Pradhan, Prajal; et al. (Springer, 2022)
Welcome to the new journal Anthropocene Science (eISSN 2731-3980), an exciting trans- and multidisciplinary international peer-reviewed journal for addressing human impact on the resilience of planet Earth, published by Springer Nature